Pesona Sukuk Ritel Seri 13 (SR013) sebagai Alternatif Investasi di Masa Pandemi Covid-19 - Aristantia, Selvia Eka (El-Qist: Journal of Islamic Economics and Business (JIEB), 2020)
This study aims to reveal how the charm of Sukuk SR013 as an alternative investment still exists even in the midst of the Covid-19 pandemic and has achieved the highest sales since online bidding was made. This study uses a netnographic method that focuses on Instagram social media. This method was chosen as a research solution in the midst of a pandemic. The netnography method is deemed suitable to be applied in this study because the researcher wants to analyze the behavior of millennial netizens on social media, especially followers of social media accounts that promote and educate about SR013. The results of this study reveal five reasons netizen investors choose to invest in this instrument. The first reason is the patriotism inherent in the souls of investors. The second reason is the benefits of getting fixed coupons. The third reason is because Retail Sukuk are traded under the concept of Sharia. The fourth reason is because of the ease of investing with a minimum investment of IDR 1,000,000.00. The fifth reason, there is clear evidence of the use of Sukuk for the country that is seen directly by investors. Key Words: Sukuk; SBSN; Netnography; Covid-19 Â  Penelitian ini bertujuan untuk mengungkap bagaimana pesona Sukuk SR013sebagai salah satu alternatif investasi masih eksis bahkan di tengah pandemi Covid-19 dan meraih penjualan tertinggi sejak dilakukan penawaran secara online. Penelitian ini menggunakan metode netnografi yang berfokus pada media sosial Instagram. Metode ini dipilih sebagai solusi penelitian di tengah masa pandemi. Metode Netnografi dirasa relevan untuk diterapkan dalam penelitian ini karena peneliti ingin menganalisis perilaku dari netizen milenial di media sosial khususnya pengikut akun media sosial yang mempromosikan dan mengedukasi mengenai SR013. Hasil dari penelitian ini mengungkap lima alasan netizen investor memilih untuk berinvestasi di instrumen ini. Alasan yang pertama ialah adanya nilai-nilai patriotisme yang melekat dalam jiwa para investor. Alasan kedua ialah adanya keuntungan yang didapat dengan mendapatkan kupon tetap. Alasan ketiga karena Sukuk Ritel ini diperdagangkan dengan konsep Syariah. Alasan keempat karena kemudahan dalam berinvestasi dengan minimal investasi sebesar Rp 1.000.000,00. Alasan kelima adanya bukti nyata dari pemanfaatan Sukuk untuk Negeri yang dilihat langsung oleh investor. Kata Kunci: Sukuk; SBSN; Netnografi; Covid-19